2021
DOI: 10.52168/bjf.2021.33.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqua-drugs and chemicals on shrimp health and production in Khulna, Bangladesh

Abstract: Present study was conducted in three different Upazilas viz., Batiaghata, Dacope and Rupsha of Khulna district, Bangladesh from August 2016 to May 2017. Data were collected through personal contact, farms and market survey and discussion with shrimp farmers and drug sellers. Farmers of the research areas used Oxolinic acid, Renamucin, Oxytetracucline, Lime, Salt, Formalin, Eco-solution, Basudin and Timsen to treat the viral, bacterial and fungal diseases. Average recovery of 55-60% and 35-40% were recorded fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…These antibiotics have been marketed under several brand names and have various active ingredients. Among the different ingredients, three active ingredients (doxycycline, colistine sulphate + vitamin premix + mineral, oxytetracycline HCl 200 mg and oxytetracycline 200 mg) are overused by fish farmers 50 . Farmers indiscriminately add these antibiotics to the supplemental feed to avoid diseases before they even have an issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These antibiotics have been marketed under several brand names and have various active ingredients. Among the different ingredients, three active ingredients (doxycycline, colistine sulphate + vitamin premix + mineral, oxytetracycline HCl 200 mg and oxytetracycline 200 mg) are overused by fish farmers 50 . Farmers indiscriminately add these antibiotics to the supplemental feed to avoid diseases before they even have an issue.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different ingredients, three active ingredients (doxycycline, colistine sulphate + vitamin premix + mineral, oxytetracycline HCl 200 mg and oxytetracycline 200 mg) are overused by fish farmers. 50 Farmers indiscriminately add these antibiotics to the supplemental feed to avoid diseases before they even have an issue. The majority of studies on the benefits of antibiotics and growth promoters on cultured aquatic animals have focused on reduced mortality or, conversely, higher survival and disease resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides antibiotics, a wide range of natural and synthetic products, including lime, salt, potassium permanganate, pesticides, fertilizers, and probiotics are used to treat, prevent diseases and improve water quality [ 32 , [40] , [41] , [42] , [43] ]. Our study found that lime, potassium permanganate, and bleaching powder (calcium oxychloride) were commonly used by fish farmers.…”
Section: Discussionmentioning
confidence: 99%
“…However, some technical barriers to trade, such as international standards and regional technical regulations in the importing countries aimed at protecting consumers from the presence of chemical residues and contaminants in traded aquaculture products associated with intensive farming, may have significant impact on the efforts in these developing countries. Different drugs and chemicals have been widely used to improve the aquaculture production (Hossain et al, 2018). A regrettable fact that, nitrofuran and chloramphenicol occupy an important place as aqua chemicals in the market of Bangladesh and the distribution as well as application of these drugs is most often by unqualified people.…”
Section: Introductionmentioning
confidence: 99%